HUBUNGAN ANTARA DURASI PENGGUNAAN MEDIA SOSIAL DENGAN KUALITAS TIDUR PADA REMAJA: STUDI DI KABUPATEN LAMONGAN - Rozi, Fahrur; Amiseno, Gurit Cokro; Sholikhah, Dwi Uswatun; Sasmito, Nanang Bagus (LPPM STIKES HUSADA JOMBANG, 2025)
Background: The continuous use of social media can impact adolescent activities. may result in sleep quality. Objectives: This study was to determine the relationship between the duration of social media use and sleep quality in adolescents in Banjargondang Village, Bluluk District, Lamongan Regency. Methods: The research design used descriptive correlation with a cross-sectional approach. in research, a sample of 48 respondents was obtained and used for accidental Sampling. Data collection tools in the form of social media use scale and PSQI questionnaires, and data analysis using Spearman's rank. Results: The results of research that have been conducted on adolescents show that most respondents who have duration of social media use (Active) with sleep quality (Poor) are 30 respondents (62.5%). Almost half of the respondents who have duration of social media use (Inactive) with sleep quality (Good) are 18 respondents (37.5%). The study found that 62.5% of adolescents who used social media actively had poor sleep quality. A significant correlation was identified (Spearman’s rho = 0.646; p = 0.001). Conclusion: Teenagers are expected to be more discerning in their use of social media to avoid developing a dependence that can negatively impact their sleep quality.